Discovering Warrants in Political Argumentation - Gallhofer, Irmtraud; Saris, Willem (Informal Logic, 2021)
Philosophers deny a proposal for actions can be deduced from arguments for or against the proposal because they may be incompatible. Nevertheless, people in general, and politicians especially, make decisions and present arguments they believe are convincing. We studied politicians who made decisions in complex situations. They spoke about possible actions, their consequences, the probabilities of these consequences and their evaluations, but rarely indicated why their arguments led to their choice. We hypothesized implicit argumentation rules involved and checked whether they predicted those choices. We found seven implicit informal logic rules involved. We also found a random sample of people made the same choices based on the same arguments, suggesting basic warrants by which people argue about decisions.